Evaluation of the best solution for the functionalization of photocatalytic, superhydrophobic, and self-cleaning properties on asphalt mixtures - Rocha Segundo Iran (EDP Sciences, 2021)
This research aims to develop asphalt mixtures with new capabilities, namely photocatalytic, superhydrophobic, and self-cleaning capabilities. Different solutions were prepared combining nano-TiO2 and micro-PTFE on water, ethyl alcohol, and dimethyl ketone with different concentrations. The solutions were sprayed over the asphalt mixtures, and the photocatalytic and superhydrophobic capabilities were evaluated via decolourization of Rhodamine B dye aqueous solution under simulated solar irradiation and Water Contact Angle (WCA) measurements, respectively. Among the combinations analysed, the best solution was TiO2-PTFE with ethyl alcohol (8 g/L), which provided a decolourization of about 60% after having spent 8 h in light exposure conditions and a superhydrophobic surface with WCA equal to 153º. Thus, this research work aims to contribute to advances in the field of clean technologies, assisting in the transition to the “Green Recovery”, which is environmentally friendly, inclusive, and sustainable.